Kronika Društva univerzitetnih profesorjev Maribor: 1962-2022 (University of Maribor Press, 2022)
The Chronicle of the Maribor University Professors Association from 1962 to 2022. The University of Maribor Professors Association (UMPA) celebrated its 60th anniversary by publishing its Chronicle. The Chronicle presents a continuation of a chronicle, which covers the period from the beginning to 2005 and was written by the Association’s former president, prof. dr. Franc Pauko, full professor. The book presents documentary materials from the records of the meetings. The editors of the Chronicle from 1962 to 2022 followed the previous Chronicle’s theme and form. They enriched the content by adding selected photographs and articles and created an authentic document on the Association, its mission and the activities of its members. UMPA was active under the patronage of the Association of High School Maribor Institutions until 1975 when the University of Maribor was established. Afterwards, it was under the patronage of the University. It moved three times during this time and often changed its name. The activities of its members and numerous events promoted the University of Maribor and vice versa. The ethical conduct of the UMPA members was always of the utmost importance. Five appendixes follow the annual overview of the Association’s activities: The Code of the University Professors of Slovenia. The list of all presidents and secretaries general of theAssociation, its honorary professors and professors emeriti.The list of elected representatives of executive boards of the Association.The list of lectures organised for the general public.